2016
DOI: 10.3390/nu8090533
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Vitamin D-Effective UVB Availability in Europe and Associations with Population Serum 25-Hydroxyvitamin D

Abstract: Low vitamin D status is common in Europe. The major source of vitamin D in humans is ultraviolet B (UVB)-induced dermal synthesis of cholecalciferol, whereas food sources are believed to play a lesser role. Our objectives were to assess UVB availability (Jm−2) across several European locations ranging from 35° N to 69° N, and compare these UVB data with representative population serum 25-hydroxyvitamin D (25(OH)D) data from Ireland (51–54° N), Iceland (64° N) and Norway (69° N), as exemplars. Vitamin D-effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
146
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(156 citation statements)
references
References 32 publications
7
146
2
1
Order By: Relevance
“…In our subsample from the NutriNet-Santé study ( N = 732), corresponding proportions were 43% in the northern regions and 31% in the southern regions. In Europe, contrary to expectations, the prevalence of low VitD status did not align perfectly with the latitude or region-based UVB doses [7,48,49,50]. Low VitD status was observed to be more frequent in mid-latitude countries (e.g., UK, Ireland, Netherlands, Germany) than in northern countries (e.g., Norway, Iceland, Finland) and a higher VitD status in southern countries (e.g., Spain, Italy, Greece) was not systematically observed.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In our subsample from the NutriNet-Santé study ( N = 732), corresponding proportions were 43% in the northern regions and 31% in the southern regions. In Europe, contrary to expectations, the prevalence of low VitD status did not align perfectly with the latitude or region-based UVB doses [7,48,49,50]. Low VitD status was observed to be more frequent in mid-latitude countries (e.g., UK, Ireland, Netherlands, Germany) than in northern countries (e.g., Norway, Iceland, Finland) and a higher VitD status in southern countries (e.g., Spain, Italy, Greece) was not systematically observed.…”
Section: Discussionmentioning
confidence: 73%
“…Low VitD status was observed to be more frequent in mid-latitude countries (e.g., UK, Ireland, Netherlands, Germany) than in northern countries (e.g., Norway, Iceland, Finland) and a higher VitD status in southern countries (e.g., Spain, Italy, Greece) was not systematically observed. This could be due to differences in sun-seeking behaviors, food intakes but also in VitD fortification policies or supplementation practices [7,48,49,50,51]. One may think that people from Northern Europe may display more awareness regarding the risk of low VitD status and thus a better VitD-related knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency is more common at higher latitude, particularly in winter, when the opportunity for sun exposure is lowest . The risk of vitamin D deficiency is greatest in the high latitude countries of the Northern Hemisphere during winter, when there is insufficient UV‐B radiation to allow vitamin D synthesis . We have previously noted the latitude gradient of decreasing incidence of IBD with increasing proximity to the Equator, particularly in the Northern Hemisphere .…”
Section: Associations Of Vitamin D and Sun Exposure With Ibd And Pibdmentioning
confidence: 99%
“…This inadequacy arose from a combination of a lack of dermal synthesis of vitamin D 3 during the winter because of limited UVB irradiation (2) and low dietary vitamin D intake (1,3). Several subsequent studies have likewise indicated inadequate vitamin D status in various population subgroups in Finland (4)(5)(6).…”
mentioning
confidence: 99%